KEMANDIRIAN DAN INTERVENSI SEBAGAI BASIS KEBERDAYAAN MASYARAKAT KAWASAN RAWA PENING - , CHANDRA BHASKARA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spatial utilization these day is focused on the paradigm of people centered development. People in the era of decentralization is no longer positioned as object but as the subject of development. Empowerment in terms of initiative and creativity has owned by people is the most important resource in human development and the material and spiritual welfare as an objective to be achieved by the development process. This study begins with curiosity about how the empowerment society was formed in utilizing the spatial resources in the Rawa Pening region. So, the objective of this study is to describe and analyze the empowerment society in utilizing the spatial resources, in terms of the influence of social capital, community institutional, and the role of external institutional. This study uses qualitative descriptive research method and phenomenology as the theoretical foundation. Based on the analysis, independent empowerment in utilize spatial resources to fulfill it living need is formed long ago and is a heritage from their ancestors. Empowerment because intervention from external institutional like government or other private also help to increase empowerment societies in Rawa Pening region. Government role in this sector is giving fund, counseling and training. With the intervention from government, society empowerment can be expected to increase with the people-oriented development programs.